1987
DOI: 10.1577/1548-8659(1987)116<574:psriwa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Stress Responses in Wild and Hatchery-Reared Rainbow Trout

Abstract: Stress‐induced changes in plasma cortisol, glucose, and chloride were more extreme in wild rainbow trout Salmo gairdneri than in hatchery‐reared fish subjected to confinement in a net and to electroshock. During 12 h of net confinement, plasma cortisol increased from resting levels of 10 ng/mL to 480 ng/mL in wild fish, and from 2 ng/mL to 155 ng/mL in hatchery fish. Plasma glucose was also higher in wild fish, increasing from 55 to 284 mg/dL, versus an increase from 58 to 196 mg/dL in hatchery fish. Plasma ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
84
1
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(103 citation statements)
references
References 0 publications
16
84
1
2
Order By: Relevance
“…Levels of plasma cortisol for rapid capture fish identified in this study were within the range of resting or baseline levels previously reported for rainbow trout (Woodward and Strange, 1987;Pankhurst and Dedual, 1994). However, levels of plasma lactate for rapid capture fish were higher than resting levels previously reported for wild (Pankhurst and Dedual, 1994) and hatchery (Milligan and Girard, 1993) rainbow trout.…”
Section: Baseline Levels Of Physiological Parameterssupporting
confidence: 73%
See 2 more Smart Citations
“…Levels of plasma cortisol for rapid capture fish identified in this study were within the range of resting or baseline levels previously reported for rainbow trout (Woodward and Strange, 1987;Pankhurst and Dedual, 1994). However, levels of plasma lactate for rapid capture fish were higher than resting levels previously reported for wild (Pankhurst and Dedual, 1994) and hatchery (Milligan and Girard, 1993) rainbow trout.…”
Section: Baseline Levels Of Physiological Parameterssupporting
confidence: 73%
“…The magnitude of a stress response and recovery time can vary depending on the severity and duration of stress, fish size, temperature, recovery conditions, developmental state, and origin of fish (e.g., stock or hatchery versus wild; Wydoski et al, 1976;Mazeaud et al, 1977;Woodward and Strange, 1987;Pickering and Pottinger, 1989;Pankhurst and Dedual, 1994;Carey and McCormick, 1998). Alagnak River rainbow trout with greater landing and handling times presumably experienced a greater peak plasma cortisol and lactate response and longer recovery period than fish captured more quickly.…”
Section: Recovery and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted in other species, that domestication and increased tameness is genetically linked to a wide array of behavioural, physiological and developmental traits and that this may be mediated via HPA and HPG axis dynamics [60]. Domestication has led to attenuated HPA reactivity in all species studied so far, while basal HPA axis activity is not necessarily affected [10,20,[22][23][24]. Cockrem [61] concludes that domestic birds (chickens, Japanese quail) have lower CORT levels after stress compared to wild species of birds (Adelie penguin, Great tit), which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have compared hypothalamic-pituitary-adrenal (HPA) axis reactivity of wild and domesticated animals and they suggest that attenuated HPA-axis reactivity in domesticates is common in many species including mice [19], rats [20], pigs [21], guinea pigs [10] silver foxes [22], mallard ducks [23] and salmonids [24]. Furthermore, activation of the HPA-axis suppresses the hypothalamic-pituitary-gonadal (HPG) axis in most animals through several mechanisms [25].…”
Section: Introductionmentioning
confidence: 99%